Comparative cost-effectiveness of Option B+ for prevention of mother-to-child transmission of HIV in Malawi. (27th March 2016) - Tweya, Hannock; Keiser, Olivia; Haas, Andreas D.; Tenthani, Lyson; Phiri, Sam; Egger, Matthias; Estill, Janne
Abstract : Objective: To estimate the cost-effectiveness of prevention of mother-to-child transmission (MTCT) of HIV with lifelong antiretroviral therapy (ART) for pregnant and breastfeeding women ('Option B+') compared with ART during pregnancy or breastfeeding only unless clinically indicated ('Option B'). Design: Mathematical modelling study of first and second pregnancy, informed by data from the Malawi Option B+ programme. Methods: Individual-based simulation model. We simulated cohorts of 10 000 women and their infants during two subsequent pregnancies, including the breastfeeding period, with either Option B+ or B. We parameterized the model with data from the literature and by analysing programmatic data. We compared total costs of antenatal and postnatal care, and lifetime costs and disability-adjusted life-years of the infected infants between Option B+ and Option B. Results: During the first pregnancy, 15% of the infants born to HIV-infected mothers acquired the infection. With Option B+, 39% of the women were on ART at the beginning of the second pregnancy, compared with 18% with Option B. For second pregnancies, the rates MTCT were 11.3% with Option B+ and 12.3% with Option B. The incremental cost-effectiveness ratio comparing the two options ranged between about US$ 500 and US$ 1300 per DALY averted. Conclusion: Option B+ prevents more vertical transmissions of HIV than Option B, mainly because more women are already on ART at the beginning of the next pregnancy. Option B+ is a cost-effective strategy for PMTCT if the total future costs and lost lifetime of the infected infants are taken into account. Abstract : Supplemental Digital Content is available in the text